Fierce Autonomy: How Girls and Young Women Impacted by Commercial Sexual Exploitation Perceive Health and Exercise Agency in Health Care Decision-Making. (July 2020) - Godoy, Sarah M.; Abrams, Laura S.; Barnert, Elizabeth S.; Kelly, Mikaela A.; Bath, Eraka P.
Prior research has examined the high health care needs and vulnerabilities faced by survivors of commercial sexual exploitation (CSE), yet their perspectives are frequently absent. We sought to understand the narratives and views of individuals affected by CSE on their bodies, health, and motivations to seek health care treatment. Twenty-one girls and young women ages 15 to 19 years with self-identified histories of CSE participated in the study. All participants had current or prior involvement in the juvenile justice and/or child welfare systems. Data collection included brief questionnaires, followed by semi-structured individual interviews. The interviews took place between March and July 2017 and were analyzed using iterative and inductive techniques, using the shared decision-making model as a guide. "Fierce Autonomy" emerged as a core theme, depicting how past traumas and absence of control led the girls and young women to exercise agency and reclaim autonomy over decisions affecting their health.